2010
DOI: 10.1111/j.1399-5618.2010.00829.x
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and subcortical white matter abnormalities in adults with remitted first‐episode mania revealed by Tract‐Based Spatial Statistics

Abstract: Our findings highlighted that white matter abnormalities were present by the time of remission of first-episode mania. The widespread occurrence of these white matter abnormalities both in first-episode mania and chronic bipolar disorder suggested that disruption of white matter cortical-subcortical networks as well as projection, associative, and commissural tracts is a hallmark of the illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 53 publications
(94 reference statements)
4
31
0
4
Order By: Relevance
“…Two recent DTI studies on euthymic bipolar patients demonstrated that callosal fractional anisotropy was significantly reduced compared with healthy subjects, suggesting abnormalities in the structural integrity of the CC (Chan et al, 2010;Macritchie et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Two recent DTI studies on euthymic bipolar patients demonstrated that callosal fractional anisotropy was significantly reduced compared with healthy subjects, suggesting abnormalities in the structural integrity of the CC (Chan et al, 2010;Macritchie et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Our finding was also in agreement with a meta-analysis of wholebrain DTI studies that was conducted in adult BD patients showing two significant clusters of decreased FA in the right side of the brain, one was located close to the parahippocampal gyrus and another was located close to the right anterior and subgenual cingulate (Vederine et al, 2011). Moreover, both studies focused on WM changes of AC in late-onset and early-onset BD patients indicated a decreased FA, which suggested that WM impairment of the AC might be existed at an early stage of the disease and partly persist into adulthood (Chan et al, 2010;Frazier et al, 2007;Wang et al, 2008a).…”
Section: Anterior Cingulatementioning
confidence: 91%
“…Bipolar disorder shows, in turn, cerebral modifications, already evident in the early stages of the disorder and related to either white or gray matter abnormalities [37,38,39]. Early and effective pharmacological treatment with mood stabilizers (such as valproate, lithium, lamotrigine and atypical antipsychotics), which may also have a neuroprotective/neurotrophic action, may act on this neurobiological impairment [40].…”
Section: Resultsmentioning
confidence: 99%